SUBJECTIVE ASSESSMENT OF AESTHETIC FEATURES OF THE LANDSCAPES OF SYUNIK REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The aesthetic assessment of the landscape is one of the important problems of aesthetics. The analysis of the work accomplished in different periods shows that there are two directions of the methodology of aesthetic assessment of landscapes in science: physical-geographic, which is based on the "objective" approach of aesthetic assessment of landscapes, and socio-geographic, in which the "subjective" approach is dominant. Combining subjective and objective approaches an attempt was made to estimate the aesthetics of the landscape of Syunik Region. In case of a subjective approach, the researcher relies on the subjective opinion of people on the impressions received from a particular landscape of the aesthetic attractiveness. The was carried out with a social survey through questionnaires prepared by M.Yu. Frolova. In order to obtain the most reliable results, the principles of selecting pictures and survey participants have been developed. Most of the pictures were taken during our tours. The survey involved 80 people, where more than 40 pictures were presented. The respondents highly appreciated those landscapes, where there is a combination of different components of the given landscape. Autumn landscapes of forested areas were rated higher than spring ones. The results of the subjective correspond to the results of the objective made by us for the landscapes of Syunik Region by 83%. Comparing the average results of the subjective with the results of the objective, we have obtained a map of the aesthetic attractiveness of the Syunik Region. The most attractive and attractive areas occupy 9.5% and 22.4% of the Syunik Region territory, respectively, unattractive areas occupy 0.2%. Obtaining a reliable result, it is recommended to use the methods of objective and subjective estimations together.
Keywords: subjective assessment; landscape aesthetics Syunik Region; social survey; questionnaires